Compressibility of arterial wall - Direct measurement and predictions of compressible constitutive models - Skacel, Pavel; Bursa, Jiri (Journal of the mechanical behavior of biomedical materials, 2019)
Volumetric compressibility and Poisson's ratios of fibrous soft tissues are analyzed in this paper on the basis of constitutive models and experimental data. The paper extends the previous work of Skacel and Bursa (J Mech Behav Biomed Mater, 54, pp. 316-327, 2016), dealing with incompressible behaviour of constitutive models, to the area of compressibility. Both recent approaches to structure-based constitutive modelling of anisotropic fibrous biomaterials (based on either generalized structure tensor or angular integration) are analyzed, including their compressibility-related aspects. New experimental data related to compressibility of porcine arterial layer are presented and compared with the theoretical predictions of analyzed constitutive models. The paper points out the drawbacks of recent models with distributed fibres orientation since none of the analyzed constitutive models seems to be capable to predict the experimentally observed Poisson's ratios and volume change satisfactory.
Keywords: Animals; pevnost v tlaku; biologické modely; Arterial wall mechanics; Hyperfit software; Compressible hyperelastic models; Anisotropy; Models, Biological; prasata; Compressibility of soft tissue; mechanický stres; Stress, Mechanical; biomechanika; Materials Testing; Arteries; Compressive Strength; Swine; testování materiálů; Poisson's ratio; zvířata; arterie; Biomechanical Phenomena